Partisipasi Mahasiswa Tadris Biologi IAIN Kudus pada Pemilihan Umum Presiden dan Wakil Presiden Tahun 2019 - Malichatin, Hanik (State Islamic Institute of Kudus (IAIN Kudus), 2019)
This study aims to describe student participation in exercising suffrage in the 2019 presidential and vice presidential elections. The method used in this study is a qualitative method with the research subject being there are 30 students from Tadris Biology of IAIN Kudus. Sample selection technique with a purposive sampling The process of retrieving data and information is done through questionnaires, interviews and literature review. The results of the study were obtained by all respondents using their voting rights in the presidential and vice presidential elections. There are several factors that influence respondents in using their voting rights, namely political awareness, the influence of mass media and political discussion, and the influence of parents and society. As many as 29 people used their voting rights because of political awareness, that as citizens who were 17 years old they had the right to vote, and 25 people used their right to vote because they were influenced by mass media and political discussion. Whereas 11 are influenced by parents and society. Individuals who have political awareness then he will have an awareness of his position in a state of life. Political participation which is based on political awareness will encourage someone to use their right to vote rationally. While the media have an influence on political participation because the media are a means for disseminating political information or campaigns.